STRATEGI MEMPERTAHANKANKAN USAHA PEDAGANG DI TENGAH PERKEMBANGAN ERA (E-COMEMMERCE) MENURUT PERSPEKTIF ISLAM PADA PEDAGANG PASAR TRADISIONAL MODERNT (PTM) KOTA BENGKULU - Hanipah, Mei Alfiani; Setiawan, Romi Adetio; Syaifuddin, Syaifuddin (ITB AAS Indonesia Surakarta, 2024)
This research aims to find out the survival strategies of traders in modern traditional markets (Ptm) amidst the rise of online shopping (e-commerce) and to find out survival strategies according to an Islamic perspective. This research uses descriptive qualitative methods for SWOT with primary and secondary data sources. The results obtained from the SWOT analysis show that the position of the modern market in Bengkulu City is strong, so the recommended strategy is the SO strategy, namely utilizing support from the government, maintaining product quality, maintaining good working relationships, costs, low production and expanding the network. Forms of competition that exist in the modern traditional market in Bengkulu City include competition on price, location, service quality and product completeness. And the strategy carried out by the modern traditional market according to an Islamic perspective is in accordance with the marketing management strategy in Islam, namely being honest in explaining goods and promoting goods, being fair in setting prices.